Comparative physiology study of side effect between Xenical and Lipo-6 Supplements which treated obese rabbets - abdulshaheed, Hayder Ghazi (Al-Qadisiyah Journal of Pure Science, 2022)
Obesity is rapidly becoming a health problem, and it is considered a metabolic disease of epidemic proportions. Obesity is also associated with many comorbidities such as hyperlipidemia, fatty liver, atherosclerosis, cancer. Use of over-the-counter weight-loss supplements has become more common in the world; Xenical and Lipo-6 are two examples of nutritional supplements that do not pass safety research before being sold to the consumer. The ability of Xenical and lipo-6 supplements on DNA fragmentation in human lymphocytes was studied, where these cells represent important defense line of the body. On other hand, thirty white rabbits Iraqis in this experiment, weighing 2.5 to 3.0 kg were employed, which divided randomly to the three group (A: Control group, B: Xenical group, C: Lipo-6 group). In the end of experiment, all animals synthesized for collection blood to complete blood count examination and then all animal scarified for taking tissues samples to histopathological examination. The results showed that, the effects of two different types of medications on DNA fragmentation in human lymphocytes were examined. Xenical, at high concentrations (500 µg/ml), caused a significant fragmentation of lymphocytes’ DNA (p ≥ 0.05); DNA fragmentation percentages were 68.5 percent after 24 hours and reached 76.4 percent after 48 hours. the lipo-6 at high concentration displayed apoptotic activity against healthy cells after 24 hours of exposure; DNA fragmentation was 80.13%. After 48 hours, the proportion of DNA fragmentation increased to 89.71 percent. As well as, the present study were conducting to determine toxicity of drug in rabbits in order to scientific information about its safety. The results of this study, reveals a histological sections for (liver, lung, heart, spleen, and intestine) in rabbits groups treated with Xenical and Lipo- 6 two capsule per day. pathological alterations in the treated rabbits’ intestines, including macrophage and lymphocyte infiltration indicating chronic inflammation, furthermore, intestine section showed Macro vesicular fatty change. The spleen histological Samples founded with highly-blood foci (bleeding), highly infiltration with lymphocytes, also section exhibit highly proliferative cells with abnormal blood collections in both groups treated with Xenical and Lipo-6,in comparative to normal spleen. the lung tissue inflammation, the production of air vacuoles, damage to the alveolar sac and found a significant RBC cast in the heart muscle.